2021
DOI: 10.33448/rsd-v10i6.16168
|View full text |Cite
|
Sign up to set email alerts
|

Feira interativa: Utilização de metodologias inovativas na educação em saúde

Abstract: Uma feira em saúde se estabelece como instrumento no processo de aprendizagem, onde permite-se experienciar metodologias criativas diversas a partir de um espaço que possibilita explorar e compartilhar conhecimentos. Neste estudo, relata-se experiências de duas edições (dezembro/2018 e março/2019) de uma feira interativa como tecnologia em saúde, vivenciadas por discentes voluntários e bolsistas, inseridos em programas universitários de extensão e iniciação tecnológica. Foram realizadas em um Centro de Ensino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…This consisted of four stations focusing on presentation of the research results with parasite viewing under the microscope, presentation of the symptoms of parasitoses, use of posters with parasitic cycles and preventive measures and a board game with questions related to enteric parasites. This fair also concluded the health education stage, informing research participants of preventive measures related to enteric parasites (Passos et al, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…This consisted of four stations focusing on presentation of the research results with parasite viewing under the microscope, presentation of the symptoms of parasitoses, use of posters with parasitic cycles and preventive measures and a board game with questions related to enteric parasites. This fair also concluded the health education stage, informing research participants of preventive measures related to enteric parasites (Passos et al, 2019).…”
Section: Resultsmentioning
confidence: 95%
“…Nessas maquetes esquemáticas, os ciclos de vida dos parasitos foram representados pelo mecanismo de infecção, forma infectante, habitat do parasito, eliminação pelo hospedeiro e contaminação do meio. (ROSSI et al, 2017;LIMA et al, 2018;ANASTASIOU;MORENO-AMOR, 2018;SANTOS JUNIOR et al, 2018;MATOS et al, 2019;PASSOS et al, 2021a).…”
Section: Resultsunclassified
“…Finally, it is revealed that educational interventions, such as the interactive health fair held by this team and arranged by Passos et al 9 , collaborate in the improvement of the knowledge about parasitic diseases in a way that contributes to the adequate prevention, treatment, and control measures of these, in addition to collaborating in the understanding of the symptoms and associations that can occur with other parasitic diseases and comorbidities 54 . According to an action carried out by Rodrigues, Scherer, and Moreira55 in a group of Community Health Agents, they observed improvement in these professionals after a guidance activity regarding the importance of drinking filtered or boiled water, adequate food hygiene, hand washing and fighting to parasite-carrying insects, which strengthened the role of knowledge multipliers in the enrolled population.…”
Section: Discussionmentioning
confidence: 99%